2023
DOI: 10.3390/plants12162955
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Easily Extractable Glomalin-Related Soil Protein Stimulates Plant Growth by Regulating Tonoplast Intrinsic Protein Expression in Lemon

Abstract: Arbuscular mycorrhizal fungi (AMF) have the function of promoting water absorption for the host plant, whereas the role of easily extractable glomalin-related soil protein (GRSP), an N-linked glycoprotein secreted by AMF hyphae and spores, is unexplored for citrus plants. In this study, the effects on plant growth performance, root system characteristics, and leaf water status, along with the changes of mineral element content and relative expressions of tonoplast intrinsic protein (TIP) genes in lemon (Citrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
2
2
3
Order By: Relevance
“…Soluble protein is an important osmoregulatory substance, which can improve the water retention capacity of cells as it accumulates [31]. Furthermore, the present study also revealed that the LWP in the tea leaves was dramatically reduced under all exogenous EE-GRSP treatments, and these findings were consistent with those of Guo et al [18] on lemon seedlings, but contrary to those of Chi et al [9] on trifoliate orange seedlings, which may be attributed to an increase in the solute concentration in tea leaves. Ultimately, exogenous EE-GRSP application accelerated nutrient accumulation in plant leaves, thereby increasing the cytoplasmic concentration and osmotic pressure [32], which may be the main reason for the decrease in the water potential.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Soluble protein is an important osmoregulatory substance, which can improve the water retention capacity of cells as it accumulates [31]. Furthermore, the present study also revealed that the LWP in the tea leaves was dramatically reduced under all exogenous EE-GRSP treatments, and these findings were consistent with those of Guo et al [18] on lemon seedlings, but contrary to those of Chi et al [9] on trifoliate orange seedlings, which may be attributed to an increase in the solute concentration in tea leaves. Ultimately, exogenous EE-GRSP application accelerated nutrient accumulation in plant leaves, thereby increasing the cytoplasmic concentration and osmotic pressure [32], which may be the main reason for the decrease in the water potential.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the application of exogenous EE-GRSP promoted the growth and increased the biomass of tea seedlings at different ranges; plant growth was optimal under the 1/2 EE-GRSP treatment, while the biomass was greatest under the 3/4 EE-GRSP treatment, which was consistent with the results from previous studies on trifoliate orange seedlings [11,18]. These results further confirmed that GRSP exerts a positive effect on plant growth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations